2011
DOI: 10.1007/s00436-011-2521-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum infection-induced changes in erythrocyte membrane proteins

Abstract: Over the past decade, advances in proteomic and mass spectrometry techniques and the sequencing of the Plasmodium falciparum genome have led to an increasing number of studies regarding the parasite proteome. However, these studies have focused principally on parasite protein expression, neglecting parasite-induced variations in the host proteome. Here, we investigated P. falciparum-induced modifications of the infected red blood cell (iRBC) membrane proteome, taking into account both host and parasite proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…The vaccine consists of host cell plasma membranes, isolated in the form of ghosts from P. chabaudi-parasitized red blood cells as described elsewhere (Wunderlich et al 1985. These ghosts contain parasite-synthesized proteins (Wunderlich et al 1988b, c), as it has been also described for plasma membranes of P. falciparum-infected erythrocytes (Fontaine et al 2012). Approximately 10 6 ghosts suspended in 100 μl Freund's complete adjuvant were injected twice on week 3 and week 1 before challenging with 10 6 P. chabaudiparasitized red blood cells (Krücken et al 2009).…”
Section: Vaccinationmentioning
confidence: 98%
“…The vaccine consists of host cell plasma membranes, isolated in the form of ghosts from P. chabaudi-parasitized red blood cells as described elsewhere (Wunderlich et al 1985. These ghosts contain parasite-synthesized proteins (Wunderlich et al 1988b, c), as it has been also described for plasma membranes of P. falciparum-infected erythrocytes (Fontaine et al 2012). Approximately 10 6 ghosts suspended in 100 μl Freund's complete adjuvant were injected twice on week 3 and week 1 before challenging with 10 6 P. chabaudiparasitized red blood cells (Krücken et al 2009).…”
Section: Vaccinationmentioning
confidence: 98%
“…In accordance, it has been recently found that autoantibodies and sera from patients suffering from diverse autoimmune conditions, but not from malaria, inhibit the in vitro growth of P. falciparum in human RBCs (Bhatnagar et al, 2011; Brahimi et al, 2011). Especially that type of autoimmunity is apparently required for protection against blood-stage malaria (Daniel-Ribeiro, 2000), that is presumably directed against autoantigens and parasite-induced neo-autoantigens on the surface of Plasmodium -infected RBCs (Wunderlich et al, 1988b,c; Fontaine et al, 2012). It is therefore not surprising that surface membranes of Plasmodium -infected RBCs can be used for protective vaccination of malaria-susceptible mice, which raises their survival from 0 to more than 80% and decreases peak parasitemia by about 30% (Wunderlich et al, 1988a; Krücken et al, 2009).…”
Section: Liver Effectors Toward Blood-stage Malariamentioning
confidence: 99%
“…Moreover, there is a vaccination technique available by which survival of mice, being naturally susceptible to malaria, can be raised from 0% to over 80% (Wunderlich et al, 1988a; Krücken et al, 2009). This technique, which uses a non-infectious vaccine consisting of surface membranes isolated from P. chabaudi -infected erythrocytes containing parasite-synthesized proteins (Wunderlich et al, 1988b,c; Fontaine et al, 2012), converts lethal blood-stage infections to take a self-healing course (Krücken et al, 2009). Upon challenging with 10 6 P. chabaudi -parasitized erythrocytes, all non-vaccinated mice succumb to malaria during the crisis phase of infection, whereas the majority of vaccinated mice survive the infections and generate long-lasting immune mechanisms against homologous re-challenge (Krücken et al, 2009).…”
Section: Introductionmentioning
confidence: 99%